It’s Kind of Like a Comfort Blanket - Rebekah Buchanan (Study and Scrutiny)
This qualitative study uses semi-structured interviews with 26 adult readers of the Harry Potter series, to explore how pleasure reading in childhood and adolescences impacts reading lives, autonomy, competency, and relatedness years after first engaging with a text. Looking at Harry Potter as a shared cultural experience allows for comparisons of reading experiences and narratives across study participants. Using Ryan and Deci’s (2000) self-determination theory, I argue for the examination into how pleasure reading in adulthood is impacted by childhood and adolescent autonomous relationships with texts. In addition, I explore how rereading the Harry Potter series has influenced participants’ life choices and cultivated long-term relationships with the texts.